Interpretation of the Hadith on Non-Cash Gold Trading from the Perspective of the Shafi‘i School and the DSN-MUI Fatwa - Akram, Mohd Dzaky (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This article aims to analyze the interpretation of the hadith on gold trading in the Shafi'i School and the fatwa of the National Council of Islamic Scholars (DSN-MUI) and assess their relevance to the practice of non-cash gold transactions. This study uses a qualitative method with a library research approach. Primary data sources consist of hadith books, classical fiqh works of the Shafi'i School, and DSN-MUI Fatwa No. 77 of 2010, while secondary data sources include scientific journals, contemporary muamalah fiqh books, and fatwas from religious institutions. Data analysis was conducted using content analysis to examine the understanding of Shafi'i scholars on riba hadith, as well as the fiqh arguments used and the interpretation of the hadith used by the National Sharia Council of the Indonesian Ulema Council (DSN-MUI). The results of the study indicate that the Shafi'i School and the DSN-MUI Fatwa have different perspectives regarding non-cash gold buying and selling. The Shafi'i School consistently emphasizes the obligation of cash transactions in gold buying and selling based on a textual understanding of the hadith and the application of qiyas to the prohibition of riba al-nasī'ah. However, in the context of modern muamalah, this view faces challenges in implementation, thus opening up space for ijtihad discourse and contextual interpretation. This confirms that the Shafi'i School's view remains relevant as a normative basis, but requires a cautious approach in responding to the dynamics of modern economic transactions. Meanwhile, the DSN-MUI Fatwa applies an integrative model of hadith interpretation, namely combining textual, rational, and contextual approaches. This fatwa emphasizes that the prohibition on buying and selling gold without cash in the hadith is not absolute, because the illat hukum (gold's function as a medium of exchange) has changed in the modern era to become an investment commodity.